Public policy and marketing research and practice - Hill, Ronald P. (Henry Stewart Talks, 2013)
Public policy process, Precipitating events, Policy development, Evaluation and assessment, New avenues of inquiry measurement, transdisciplinary research, impact, stakeholders, tipping points, Challenging our view of consumption